A Cytokine That Is Involved in Immune Responses in Chronic Hepatitis B Virus Patients - Noor R. Abady; Zeana Shakir Al-Al Hindi (Medical Journal of Babylon)
Abstract Background: The present research examines the part interleukin-17 (IL-17) plays in the progression of liver disease in people infected with the long-term hepatitis B virus. A proinflammatory cytokine called IL-17, linked to a number of autoimmune disorders, was examined in serum samples taken from different participant groups. Objective: The aim of this study is to examine the levels of IL-17 in various participant groups and understand any possible influence on the development and course of liver fibrosis. Materials and Methods: There were four groups in the study: asymptomatic HBsAg carriers (n = 42), chronic hepatitis B (CHB, n = 57), liver cirrhosis (LC, n = 59), and the normal control group (n = 80). an Enzyme-Linked was used to measure the amounts of IL-17, while reverse transcription polymerase chain reaction was used to find IL-17 mRNA in peripheral blood mononuclear cells (PBMC). Results: Liver disorders such as cirrhosis and CHB are associated with elevated levels of IL-17. Both the subjects’ serum and PBMCs showed these elevated IL-17 levels, demonstrating a strong correlation with inflammation. These findings highlight the significant function of IL-17 in the possible management or treatment of a variety of liver-related conditions. Conclusion: The investigation comes to the conclusion that IL-17 levels increase as liver disease severity increases, suggesting that it is involved in the development of fibrosis and the progression of the disease. Gaining insight into the function of IL-17 may help develop more effective therapies for CHB and LC patients. It is crucial to conduct further research in this area to develop tailored therapeutics.